The Role of Village Library to Improve Literacy Program for Community Welfare - Alex Abdu Chalik; Fransiska Timoria Samosir (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2022)
Background of study: The village library aims to improve the welfare of the community in the village. This library concept is called social inclusion-based library. Lentera Village Library also participates in efforts to improve the welfare of the people in the Tepi Laut Village through various efforts and activities in the development of the village library and community empowerment. Purpose: to look at the role of the village library in improving welfare literacy for the people in Tepi Laut Air Napal. Method: The research method in this research is using a qualitative approach. The informants in this study consisted of 5 informants, namely the village head, the person in charge of the library, the community, and students. The research was conducted using interviews and observation. Findings: The library in connectivity already has library infrastructure, in content the library has had welfare empowerment collections but it has not been said to be optimal because of the small number. Indicator Human where human resources in library management have not been said to be optimal because they still do not have the right manager. Conclusion: The library has empowered the community in improving literacy in community welfare and several forms of activities. However, it cannot be said to be optimal due to the unavailability of adequate collections and people who do not have the determination to use library services.